Les dispositifs de scolarisation des enfants et jeunes migrants en France : des producteurs de “scolarités contraintes” - Maïtena Armagnague; Alexandra Clavé-Mercier; Marion Lièvre; Anne-Claudine Oller (Cahiers de la Recherche sur l'Education et les Savoirs, 2019)
In France, the education of children and young migrants is often organised in parallel with the common law, as they attend special programmes for students with “special educational needs” set up by the French Ministry of National Education. Based on a survey conducted in six primary and secondary schools in three school districts in France, this article aims to question the new specific forms of education called Pedagogical Units for Allophone newcomer Students (UPE2A), by analyzing how they structure the schooling of these students. Looking at the functioning and the organization of these schooling arrangements and exploring the school experience of the students, this article will highlight how the UPE2A can be considered as constrained and constraining specific educational arrangements for the various actors involved, and sometimes undermining the spirit of school law as it is thought by the legislator.